Pengembangan Media Pembelajaran Augmented Reality (AR) Berbasis Assemblr Edu Pada Pembelajaran IPAS Kelas V di SDN 1 Sepit - Husna, Asmaul; Alwi, Mijahamuddin; Fadilah, Dina (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study aims to develop Augmented Reality (AR) learning media based on assemblr edu in science learning for grade V at SDN 1 Sepit. This study is a type of Research and Development (R&D) research using the ADDIE development model which consists of 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. This research was conducted on all grade V students of SDN 1 Sepit, with a total of 30 students. The data collection techniques used in this study were in the form of expert team validation questionnaires and student response questionnaires on assemblr edu-based AR learning media which were analyzed using descriptive analysis techniques using a five-point scale for expert team validation and a four-point scale for student response questionnaires. The results of this study indicate that the validation of material experts is in the "Very Good" category with a score range of X> 54.48 and a total score of 60 and an average of 4.61. The results of the media expert validation test are in the "Very Good" category with a score range of X> 54.48 with a total score of 58 and an average of 4.46. Meanwhile, the results of the student response questionnaire that has been conducted with a total of 30 students are in the "Very Good" category with a percentage of 87%, a total score of 1,263, and an average value of 42.1. So it can be concluded, the Augmented Reality (AR) learning media based on assemblr edu in class V Science learning at SDN 1 Sepit is suitable for use as a support for learning activities at school. Abstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran Augmented Reality (AR) berbasis assemblr edu pada pembelajaran IPAS kelas V di SDN 1 Sepit. Penelitian ini merupakan jenis penelitian Research and Development (R&D) dengan menggunakan model pengembangan ADDIE yang terdiri dari 5 tahapan, yaitu: 1) Analysis (Analisis), 2) Design (Desain), 3) Development (Pengembangan), 4) Implementation (Implementasi), 5) Evaluation (Evaluasi). Penelitian ini dilakukan pada seluruh siswa kelas V SDN 1 Sepit yaitu dengan jumlah 30 siswa. Adapun teknik pengumpulan data yang digunakan dalam penelitian ini yaitu berupa angket validasi tim ahli dan angket respon siswa terhadap media pembelajaran AR berbasis assemblr edu yang dianalisis dengan teknik analisis deskriptif menggunakan skala lima untuk validasi tim ahli dan skala empat untuk angket respon siswa. Hasil penelitian ini menunjukkan bahwa validasi ahli materi berada pada kategori “Sangat Baik” dengan rentang skor X > 54,48 dan jumlah skor 60 serta rata-rata 4,61. Hasil uji validasi ahli media berada pada kategori “Sangat Baik” dengan rentang skor X > 54,48 dengan jumlah skor 58 dan rata-rata 4,46. Sedangkan hasil angket respon siswa yang sudah dilakukan dengan jumlah responden 30 siswa berada pada kategori “Sangat Baik” dengan persentase 87%, jumlah skor 1.263, serta nilai rata-rata 42,1. Sehingga dapat disimpulkan, media pembelajaran Augmented Reality (AR) berbasis assemblr edu pada pembelajaran IPAS kelas V di SDN 1 Sepit layak digunakan sebagai penunjang kegiatan pembelajaran di sekolah.